Pertumbuhan dan Mortalitas Ikan Kuro (Eleutheronema tetradactylum) yang Didaratkan di Pelabuhan Perikanan Nusantara Kabupaten Merauke - Kusmita, Ranny; Sunarni, Sunarni; Saleky, Dandi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This research aimed to determine the size structure, length-weight relationship, growth, and mortality of kuro fish (Eleutheronema tetradactylum) that landed on Nusantara Fishery Harbour, Merauke District. The samples were taken off in August-October 2022 at Nusantara Fishery Harbour, Merauke District. The metusedsing was a purposive sampling method. The measured data was the total length and weight body of kuro fish. The size structure and length-weight relationship of kuro fish were analyzed using Microsoft Excel. Meanwhile, the growth and mortality were analyzed using the FISAT II application. The result analysis shows that the range of E. tetradactylum total length landed on Nusantara Fishery Harbour is 430 – 1030 mm with a weight range of 92 – 3613 grams. The length-weight relationship of E. tetradactylum has the allometric negative growth pattern with equation W = 0,0016L2,1167 in August, W = 0,0017L2,1134 in September, and W = 0,0017L2,1077 in October. The analysis of E. tetradactylum’s growth parameter shows the value L∞ = 1053 mm, K = 0,51/year, and t₀ = -0,1201 year. The result mortality analysis of E. tetradactylum shows the total mortality (Z) was 0,78/ year, natural mortality was 0,43/year, fishing mortality (F) was 0,35/year, and exploitation rate was 0,45/year.